A Needs Analysis of Reading Media to Support Reading Engagement and Quality Education among Early Childhood Students - Ni Wayan Ayu Sri Ardiana Sari; Luh Gd Rahayu Budiarta; Ni Luh Putu Era Adnyayanti (Yayasan Zia Salsabila, 2026)
Early childhood skills play a crucial role in developing literacy skills while instilling relevant educational values, including quality education (SDG 4). However, classroom reading instruction is still dominated using simple media focused on vocabulary recognition and unable to optimally support student engagement. This study aims to analyze the needs of teachers and students for reading media that can increase reading engagement while integrating the values of quality education. This study used a qualitative descriptive approach with a needs analysis method conducted at PAUD Pelita Kasih Singaraja. Data were collected through observations of classroom reading activities and semi-structured interviews with teachers. The results of this study indicate that student reading engagement is still low, characterized by a lack of attention, participation, and interaction during reading activities. This condition is influenced by media limitations in terms of size, variety, and visual appeal. Teachers also expressed the need for reading media that are more engaging, interactive, and appropriate to the characteristics of early childhood. Therefore, developing reading media in the form of large books that integrate the values of quality education is seen as a potential solution to increase reading engagement while instilling an understanding of the importance of early education.